Anti‐inflammatory peptides and metabolomics‐driven biomarkers discovery from sea cucumber protein hydrolysates. Issue 8 (15th July 2021) - Zhang, Xuanming; Li, Haonan; Wang, Lizhen; Zhang, Shanshan; Wang, Fengxia; Lin, Houwen; Gao, Sheng; Li, Xiaobin; Liu, Kechun
Abstract : Abstract: The hydrolysates from Apostichopus japonicus sea cucumber are an important source of nitrogen that may be added to foods. We evaluated the effect of A. japonicus hydrolysates on inflammation‐associated leukocyte recruitment. The results revealed that leukocyte migration to the site of injury was significantly blocked by AJH‐1 (<10 kDa), suggesting a protective effect against CuSO4 ‐induced neuromast damage in a zebrafish model. Based on liquid chromatography/time‐of‐flight/mass spectrometry, and metabolomic analysis, the nine biomarker candidates in AJH‐1 were Val, Ala‐Pro‐Arg, Gly‐Lys, Asp propyl ester, Glu methyl ester, His butyl ester, Ile‐Ala‐Ala‐Lys, Tyr‐Lys, and Asn‐Pro‐Gly‐Lys. We used molecular docking to predict the binding affinity and docked position of the peptides onto the angiotensin converting enzyme (ACE). All the identified peptides had adequate binding affinity toward ACE, especially peptides Ala‐Pro‐Arg and Gly‐Lys. These peptides may be used in the development of therapeutic foods. Practical Application: The study revealed the anti‐inflammatory properties of the fractionated sea cucumber protein hydrolysate (<10 kDa). The characteristic peptides may be used as functional ingredients in nutraceutical foods and beverages.